Perioperative management of aortic stenosis in patients undergoing non-cardiac surgery - Herrera, Roberto A.; Smith, Mark M.; Mauermann, William J.; Nkomo, Vuyisile T.; Luis, Sushil Allen (Frontiers in Cardiovascular Medicine, 2023)
Aortic stenosis (AS) is one of the most common cardiac valve pathologies in the world and its prevalence increases with age. Although previously associated with increased perioperative mortality, more recent studies suggest mortality may be decreasing. Recent guidelines suggest that major non-cardiac surgery can be performed safely in asymptomatic severe aortic stenosis patients with close hemodynamic monitoring. Amongst symptomatic patients, guidelines recommend aortic valve intervention prior to major non-cardiac surgery, due to a reduction in the incidence of post-operative heart failure and improved long-term overall survival. This review provides a comprehensive review of the perioperative management of patients with severe aortic valve stenosis.